Effects of pullet housing on bone development in aviary-housed Dekalb White hens - Maja M. Makagon; Allison N. Pullin; Christina B. Rufener; John Tarlton; Michael Toscano; Richard A. Blatchford (Poultry Science)
ABSTRACT: The skeletal health of laying hens improves when birds are given opportunities to perform load-bearing movements with elevated structures, such as perches. We investigated how early access to elevated structures varying in complexity and height would affect bone quality and subsequent keel bone fractures in a layer multitiered aviary. Female Dekalb White pullets were reared in floor pens furnished with floor perches (FL), single-tiered aviaries (ST), or 2-tiered aviaries (TT; n = 5 pens/treatment) through 16 wk of age. At 17 wks, all structures were replaced with identical multitiered layer aviaries. The keel, both tibiae, and both humeri were collected from 60 euthanized birds from each rearing treatment at 8, 16 and 30 wk of age, and analyzed with dual X-ray absorptiometry (DEXA) for bone mineral density and length. At 18, 26, 28, and 30 wk of age, 10 focal hens/pen were radiographed repeatedly and the presence, severity of keel bone fractures were assessed with a tagged visual analogue scale. The number of fractures was also recorded. At 16 wk of age, FL pullets had lower BMD of the tibia (P = 0.003), keel (P = 0.013), and humerus (P = 0.004) compared to ST and TT pullets. Most of the observed treatment differences disappeared after pullets were transferred to the aviary. BMD continued to increase for all hens through 30 wk of age. Pullet rearing did not affect the presence or severity of keel bone fractures, or number of new fractures incurred between ages (P > 0.05). The prevalence and severity of keel bone fractures increased between 26 to 28 wk and remained high to 30 wk of age (P < 0.0001). Hens experienced more new fractures between 26 to 30 wk than between 18 to 26 wk of age (P = 0.0046). The effects of pullet housing on bone quality were short-term when hens had access to adult housing with multiple opportunities for load-bearing movements. Keel fractures with minor severity were high in prevalence reflecting the use of radiography to assess this injury.